Use of eye tracking method according to individual differences: A review from the perspective of gender, personality structure, and birth - Alpsülün, Mustafa; Balikçi, Hasan Celal; Ozek, Müzeyyen Bulut (IGI Global, 2024)
In the study, the effects on the design of learning environments were evaluated by considering gender, personality structures and birth order, which are considered as individual differences. Evaluation process eye tracking method was used. In the research, random assignment pattern paired from quasi-experimental research patterns was applied. Nineteen students from a public university participated in the research. To collect the data, a form containing demographic information, the information of the student's gender, age, along with the introverted or extroverted personality structure, and the number of children in the nuclear family were given. Data on eye movements were obtained with the eye tracking tool used while students were studying with materials. As a result of the research, the students have different individual differences, and they have made inferences about the differences in learning with the eye movements they have made in learning materials and various suggestions have been made. © 2024, IGI Global. All rights reserved.